Land plot size, machine use and agricultural intensification in China - Liu, Yanyan; Zhou, Yuan (International Food Policy Research Institute, 2019)
China has experienced unprecedented economic achievement for more than three decades and remains one of the fastest growing economies in the world. Rapid urbanization and development of the non-farm economy have led to massive movements of labor from rural to urban areas, leaving agricultural production mostly in the hands of female and senior farmers. Due to considerable surplus labor in rural areas, these changes did not raise concerns about agricultural production until recently, when the rural real wage experienced a sharp rise, signaling the exhaustion of this surplus. Since 2010, China has changed from a net exporter to a net importer of grains. Currently, China’s self-sufficiency ratio of wheat, rice and corn is about 95%. About 80% of consumed soybean and other agri-products, such as milk and sugar, are imported. As the world's most populous country, further reduction of self-sufficient ratio of major agri-products could lead to problems in food security world-wide. In order to maintain agricultural production as labor costs continue to rise, agricultural labor input will need to be substituted with machine input. China's farming system, like that of many Asian Countries, is characterized by small landholdings, a high degree of land fragmentation, and high intensification at both the intensive and extensive margin. Although China has experienced rapid farm mechanization in recent decades thanks to the rapid development of machinery rental markets, the extent to which mechanization can be realized in China's farming system remains a critical question. Small plot size poses serious constraints for mechanization because of scale economies of machine. In addition, a considerable amount of China's land is located in hills or mountains, posing further difficulties for mechanization. Recently we completed a study to explore the extent to which small plot size deters mechanization in China and the implications for agricultural production, specifically the number of cultivating seasons per year. In our field trips in China, we often observed that small plots were less frequently cultivated; the farmers we interviewed attributed this reduced intensification to the difficulty of using machines on small plots, especially if these plots are in mountainous and hilly areas. Cultivating in these small plots become less worthwhile when labor costs increase.